Contemporary management of the neck in nasopharyngeal carcinoma. Issue 6 (29th March 2021) - Ng, Wai Tong; Tsang, Raymond K. Y.; Beitler, Jonathan J.; de Bree, Remco; Coca‐Pelaz, Andrés; Eisbruch, Avraham; Guntinas‐Lichius, Orlando; Lee, Anne W. M.; Mäkitie, Antti A.; Mendenhall, William M.; Nuyts, Sandra; Rinaldo, Alessandra; et al.
Abstract: Up to 85% of the patients with nasopharyngeal carcinoma present with regional nodal metastasis. Although excellent nodal control is achieved with radiotherapy, a thorough understanding of the current TNM staging criteria and pattern of nodal spread is essential to optimize target delineation and minimize unnecessary irradiation to adjacent normal tissue. Selective nodal irradiation with sparing of the lower neck and submandibular region according to individual nodal risk is now emerging as the preferred treatment option. There has also been continual refinement in staging classification by incorporating relevant adverse nodal features. As for the uncommon occurrence of recurrent nodal metastasis after radiotherapy, surgery remains the standard of care.